Climate Adaptation Mechanisms in Marine Fish (Zoological Archives: An International Journal, 2026)
Marine fish populations are responding to ocean warming and acidification through phenotypic plasticity, range shifts,and evolutionary adaptation, but the relative contributions of these mechanisms and the pace of adaptive response varysubstantially across taxa and ocean regions. This study characterised climate adaptation mechanisms across eightcommercially important and ecologically keystone marine fish species -- Atlantic cod (Gadus morhua), Europeananchovy (Engraulis encrasicolus), European sardine (Sardina pilchardus), Atlantic mackerel (Scomber scombrus),European seabass (Dicentrarchus labrax), gilthead seabream (Sparus aurata), Atlantic herring (Clupea harengus), andturbot (Scophthalmus maximus) -- using long-term morphometric and phenological time series (1998-2024), commongarden thermal tolerance experiments on 2,840 individuals, and genome-wide FST outlier scans (RADseq; 18,420 SNPloci from 284 individuals across thermal gradient populations) to partition plastic and evolutionary components of thermalresponse. Mean spawning date advanced by 8.4 +/- 2.4 days per decade across all species (r = -0.74 with March SST; p< 0.001), with strongest advancement in anchovy (14.4 +/- 3.2 days/decade) and weakest in cod (4.8 +/- 1.8days/decade). Critical thermal maximum (CTmax) increased significantly along a north-south SST gradient in anchovy,sardine, and seabass (FST outlier loci in candidate thermal tolerance genes; 28-42 FST outlier SNPs per species, all p FST in three of eight species, indicating directional natural selection on thermal tolerance. A ClimateVulnerability Index (CVI) integrating phenological plasticity, thermal adaptation capacity, and projected SST changeranked cod as the most vulnerable and anchovy as the most adaptable species in the study assemblage, with directimplications for fisheries management under climate change.